The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/01.tp.0000266555.06635.bf
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Toxicity and Vascular Endothelial Growth Factor Release From Islet and Renal Cell Lines

Abstract: Presently, sirolimus (rapamycin) is used as both induction and maintenance immunosuppression in solid organ transplants, including whole pancreas and kidney, and islet transplantation. Sirolimus has been suggested to have deleterious effects on islet beta-cell and renal function. We investigated the effect of sirolimus on the viability of islets, podocytes, and renal tubular cells. Sirolimus reduced the viability of islets and HK-2 human proximal renal tubular cells in vitro. This toxic effect was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
2
23
0
5
Order By: Relevance
“…This finding was confirmed by electron microscopy. These data are in line with in vitro data of Laugharne et al, 25 who found podocyte culture cells not to be influenced by rapamycin treatment. In addition, we evaluated the expression of the endothelial cell marker PECAM-1 in kidneys of rapamycin-and vehicle-treated mice and found PECAM-1 to be significantly decreased.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding was confirmed by electron microscopy. These data are in line with in vitro data of Laugharne et al, 25 who found podocyte culture cells not to be influenced by rapamycin treatment. In addition, we evaluated the expression of the endothelial cell marker PECAM-1 in kidneys of rapamycin-and vehicle-treated mice and found PECAM-1 to be significantly decreased.…”
Section: Discussionsupporting
confidence: 82%
“…To evaluate whether podocytes or endothelial cells, both potent producers of VEGF, 16,25 are harmed by rapamycin treatment, we performed real-time PCR for the detection of the podocyte marker nephrin and the endothelial cell marker …”
Section: Vegf-a Expression In the Kidney Was Significantly Decreased mentioning
confidence: 99%
“…A sirolimus treatment group was chosen as a positive control of drug induced toxicity on β-cell engraftment based on previous reports of this phenomenon. 20,21 The first day following transplant on which recipeints began to maintain non-fasting blood glucose less than 12.0 mM, defined as normoglycemia, was no different between AEB and vehicle treated controls ( Fig. 2A and p = 0.40).…”
Section: Aeb071 (Sotrastaurin) Does Not Exhibit Toxic Effects On Humamentioning
confidence: 99%
“…6,7,[9][10][11]13 Here, we show that it also does not have toxic effects on glucose homeostasis. In clinical pancreatic islet transplant, sirolimus is a commonly used immunosuppressive agent and has been shown to have negative effects on β-cell function and be diabetogenic in some, 4,5,20 but not all, animal models of β-cell function. 27,28 Our findings support continued investigation into AEB as an alternate immunosuppressive agent since it provides clear benefit over current immunosuppressive agents insofar as it has no detectable toxicity on β-cells nor glucose homeostasis.…”
Section: Š2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The improvement of the immunosuppression protocol accounts for the present success of islet transplantation [57] . Encapsulation can protect allogeneic islets from immunity without using immunosuppressants.…”
Section: Cell Sourcesmentioning
confidence: 99%